2011
DOI: 10.5115/acb.2011.44.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Accessory muscle in the forearm: a clinical and embryological approach

Abstract: Muscular variations of the flexor compartment of forearm are usual and can result in multiple clinical conditions limiting the functions of forearm and hand. The variations of the muscles, especially accessory muscles may simulate soft tissue tumors and can result in nerve compressions. During a routine dissection of the anterior region of the forearm and hand, an unusual muscle was observed on the left side of a 65-year-old male cadaver. The anomalous muscle belly arose from the medial epicondyle approxiamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A subsequent review of 5,000 cadaveric dissections of the forearm did not identify any such variations related to FCU (ANG, ROZEN, VALLY et al, 2010). Ciftçioğlu, Kopuz, Corumlu et al (2011) reported an unusual muscle on the left side of a 65-year-old male cadaver. The anomalous muscle belly arose from the medial epicondyle approximately 1 cm posterolateral to the origin of the normal FCU muscle, and from the proximal part of the FDS muscle.…”
Section: Other Muscles Of the Anterior Compartmentmentioning
confidence: 96%
“…A subsequent review of 5,000 cadaveric dissections of the forearm did not identify any such variations related to FCU (ANG, ROZEN, VALLY et al, 2010). Ciftçioğlu, Kopuz, Corumlu et al (2011) reported an unusual muscle on the left side of a 65-year-old male cadaver. The anomalous muscle belly arose from the medial epicondyle approximately 1 cm posterolateral to the origin of the normal FCU muscle, and from the proximal part of the FDS muscle.…”
Section: Other Muscles Of the Anterior Compartmentmentioning
confidence: 96%
“…One of the main theories is that those masses begin to differentiate into the muscles through apoptotic mechanisms and growth factors, thus, giving shape and appearance of the muscles [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, The aFCUM may simulate a ganglion or a soft tissue tumor. 2 The ulnar artery could also be a target to compression, as the presence of more muscle mass in the fascial compartment would cause more pressure on this vessel, thus, provoking a decreased local blood flow either during forearm flexion or even in stationary position. 15 The clinical diagnosis of an accessory muscle belly should be kept in mind when there is a soft and palpable mass at the wrist associated with flexion deformities, albeit not a constant symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the importance of reporting anatomical variations to provide knowledge and further expand the surgeon's awareness. 2,3 Furthermore, the FCUM has been used as local and free muscular flap in soft-tissue reconstruction surgery, as well as in tendon transfer procedures. 5 As the tip of the olecranon has a thin and movable skin, postoperative complications of total elbow arthroplasty are not uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation